Social protection system and defence of human and peoples’ rights in Africa:: emergence and perspectives - Chaimite, Augusto Checue (Atâtôt - Interdisciplinary Journal of Human Rights (UEG), 2021)
This article aims to address the creation of the Organization of African Unity (OAU), and in a profound and critical way, the system for the protection of human and peoples’ rights in Africa. As it is dominant, the African system for the protection of human rights developed late compared to the other regional protection systems existing in the world, mainly motivated by the European colonization that subjugated the continent for centuries. In this research article, we intend to discuss the form of organization of institutions for the protection and enforcement of human rights in the regional system, above all, the mechanisms that are available to citizens to enforce their rights when all internal-state resolution mechanisms are exhausted. of conflicts. The research methodology is qualitative with contribution to the dialectical-historical method. It is believed that the research can contribute to a serious, in-depth and critical analysis and discussion on the system for the protection of human and peoples’ rights in Africa.